Resistance Index of Penicillin-Resistant Bacteria to Various Physicochemical Agents. (31st January 2012) - Kazemi, M.; Kasra Kermanshahi, R.; Heshmat Dehkordi, E.; Payami, F.; Behjati, M.
Abstract : Widespread use of various antimicrobial agents resulted in the emergence of bacterial resistance. Mechanisms like direct efflux, formation, and sequestration of metals and drugs in complexes and antiporter pumps are some examples. This investigation aims to investigate the resistance pattern of penicillin-resistant bacterial strains to some physicochemical agents. Sensitivity/resistance pattern of common bacterial strains to antimicrobial agents were evaluated by disk diffusion assay. Broth and agar dilution method were used for determination of minimum inhibitory concentration and minimal bactericidal concentration. The impact of UV ray on the bacterial growth under laminar flow hood was measured using photonmeter. Our data demonstrates that the most prevalent metal resistance was against arsenate (95.92%), followed by cadmium (52.04%) and mercury (36.73%). There was significant difference between cetrimide resistances among studied microbial strains especially for P. aeruginosa (P < 0.05 ). High rate of pathogen resistance to various antibacterial agents in our study supports previously published data. This great rate of bacterial resistance is attributed to the emergence of defense mechanisms developed in pathogens. The higher general bacterial resistance rate among Staphylococcus strains rather than E. coli and P. aeruginosa strains draws attention towards focusing on designing newer therapeutic compounds for Staphylococcus strains.